MODELING THE MANIFESTATIONS OF THE HUMAN FACTOR OF THE MARITIME CREW - Nosov, P. S.; Palamarchuk, I. V.; Safonov, M. S.; Novikov, V. I. (Science and Transport Progress, 2018)
Purpose. The article investigates the trajectories of the watch team members in maritime transport that lead to a decrease in the level of security. A formal apparatus is proposed, as well as software and hardware to identify the location of members of the watch team during the execution of complex maneuvers. Methodology. In the course of constructing the mathematical model, the most common schemes of interaction of watch members at the time of performing complex maneuvers were considered. The general problem was considered as a series of watchkeeping interactions that solve micro-tasks of ship control at a certain moment. As a result of simulation it is determined that a key role is played by the first mate, who is the most likely to deviate from the instructions, because of excessive activity or passivity in actions. Also, interaction models of members of the watchkeeping service within the framework of a multi-day ship passage are considered. Findings. Research shows that the formation of established interactions depends on the level of experience and qualifications of the members of the watchkeeping service. Overly active relocation of the mate, as well as function duplication of individual members of the watchkeeping service adversely affects the safety level in ship management. Software and hardware tools are proposed that allow identifying the location and movements of the watch team members, indicating deviations from the watchkeeping instructions for maritime transport. Originality. The authors for the first time developed software and hardware for analyzing the movements of the watchkeeping service members, allowing identifying violations of official instructions. Practical value. Based on the developed software and hardware identification of positions and movements of the members of the watchkeeping service, it becomes possible to more effectively manage the process of training navigators during simulator practice on the basis of the navigation simulator NTPRO 5000 at the Kherson State Maritime Academy, Ukraine. These studies can also be useful in studying the discipline «Organization of the crew actions in extreme conditions».